2010
DOI: 10.1108/09696471011082385
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment in the blog space

Abstract: Purpose: The purpose of this paper is the presentation of a new method for blog quality assessment. The method uses the temporal sequence of link creation events between blogs as an implicit source for the collective tacit knowledge of blog authors about blog quality. Design/methodology/approach: The blog data are processed by the novel method for the assessment of blog quality. The results are compared to Google Page Rank with respect to the Gold Standard, the BlogRazzi Bookmark Rank. Findings: The method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…34,42,43 • Frequency of non-indexed WOS sources and their indexing in DBLP and Google Scholar (for each selected study) can be seen in Appendix B, Tables B5-B7 or can be seen in Figures 2 and 3 Valuable information/knowledge can come from articles, blog posts, and so on that are created outside of the academic world. 44 Such knowledge/information literature is (generally) not covered by Google Scholar. As our results showed that almost 98% of non-indexed references are indeed indexed by Google Scholar, this would mean that SE literature tends to avoid informal literature in the sense of blog posts, white papers, and so on.…”
Section: Research Methodology and Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,42,43 • Frequency of non-indexed WOS sources and their indexing in DBLP and Google Scholar (for each selected study) can be seen in Appendix B, Tables B5-B7 or can be seen in Figures 2 and 3 Valuable information/knowledge can come from articles, blog posts, and so on that are created outside of the academic world. 44 Such knowledge/information literature is (generally) not covered by Google Scholar. As our results showed that almost 98% of non-indexed references are indeed indexed by Google Scholar, this would mean that SE literature tends to avoid informal literature in the sense of blog posts, white papers, and so on.…”
Section: Research Methodology and Descriptive Statisticsmentioning
confidence: 99%
“…Valuable information/knowledge can come from articles, blog posts, and so on that are created outside of the academic world 44 . Such knowledge/information literature is (generally) not covered by Google Scholar.…”
Section: Research Methodology and Descriptive Statisticsmentioning
confidence: 99%